Standardisation of ACPA tests: evaluation of a new candidate reference preparation. Issue 10 (13th June 2022) - Van Hoovels, Lieve; Studholme, Lucy; Vander Cruyssen, Bert; Sieghart, Daniela; Bonroy, Carolien; Nagy, Eszter; Pullerits, Rille; Čučnik, Sasa; Dahle, Charlotte; Heijnen, Ingmar; Bernasconi, Luca; Benkhadra, Farid; et al.
Abstract : Introduction: Commercial assays measuring antibodies to citrullinated protein/peptide (ACPA) show poor quantitative agreement. The diagnostic industry has never adopted the International Union of Immunological Societies-Centers for Disease Control and Prevention (IUIS-CDC) ACPA reference standard. Recently, the National Institute for Biological Standards and Control (NIBSC) prepared a new candidate ACPA standard (18/204). We evaluated both reference materials using different commercially available ACPA assays. Materials and methods: This is an international study in which the NIBSC candidate ACPA standard and the IUIS-CDC ACPA reference material were analysed together with 398 diagnostic samples from individuals with rheumatoid arthritis (RA) and in 1073 individuals who did not have RA using nine commercial ACPA assays. Results: For both reference materials and samples from individuals with RA and individuals who did not have RA, there were large differences in quantitative ACPA results between assays. For most assays, values for the IUIS-CDC standard were lower than values for NIBSC 18/204 and the IUIS-CDC/NIBSC ratio was comparable for several, but not all assays. When NIBSC 18/204 was used as a calibrator, an improvement in alignment of ACPA results across several of the evaluated assays was obtained. Moreover, NIBSC 18/204 could align clinical interpretation for some but not all assays. Conclusion: Adoption of an international standard for ACPA determination is highly desirable. The candidate NIBSC 18/204 standard improved the standardisation and alignment of most ACPA assays and might therefore be recommended to be used as reference in commercial assays.